2017
DOI: 10.5004/dwt.2017.21236
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of blackwater co-digestion on biogas production in the municipal wastewater treatment sector using pilot-scale UASB and CSTR reactors

Abstract: a b s t r ac tThe performance of two pilot-scale anaerobic reactors for blackwater co-digestion was studied as an attempt to investigate the transition of current wastewater infrastructures to source-separated sanitation. The focus of this study was to assess the feasibility of blackwater co-digestion at conventional wastewater treatment plants. Two scenarios were investigated; in scenario one, blackwater was co-digested with municipal sewage sludge in a 630 L continuous stirred-tank reactor (CSTR). In scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In general, it can be observed that all the physical and chemical properties of BW is higher than both MWW and the BWMWW. (Wendland, 2008;Abdel-Shafy et al, 2017;Wasielewski et al 2017).…”
Section: Impact Of Bw On Mwwmentioning
confidence: 99%
“…In general, it can be observed that all the physical and chemical properties of BW is higher than both MWW and the BWMWW. (Wendland, 2008;Abdel-Shafy et al, 2017;Wasielewski et al 2017).…”
Section: Impact Of Bw On Mwwmentioning
confidence: 99%